Contract between St. Paul's Episcopal Church & Ernest L. McCoy, Architect, AIA, for a Parish Hall 1947 - St. Paul’s Episcopal Church (Bakersfield, Calif.); McCoy, Ernest; McCoy, Ernest
Report from architect on the expected cost of constructing new Parish hall, and signed contract for the work to be completed.